Frequency, prognostic impact, and subtype association of 8p12, 8q24, 11q13, 12p13, 17q12, and 20q13 amplifications in breast cancers - Viens Patrice; Zemmour Christophe; Finetti Pascal; Geneix Jeannine; Esterni Benjamin; Gelsi-Boyer Véronique; Monville Florence; Cervera Nathalie; Ginestier Christophe; Sircoulomb Fabrice; Letessier Anne; Charafe-Jauffret Emmanuelle; et al. (BMC Cancer, 2006)
Abstract Background Oncogene amplification and overexpression occur in tumor cells. Amplification status may provide diagnostic and prognostic information and may lead to new treatment strategies. Chromosomal regions 8p12, 8q24, 11q13, 17q12 and 20q13 are recurrently amplified in breast cancers. Methods To assess the frequencies and clinical impact of amplifications, we analyzed 547 invasive breast tumors organized in a tissue microarray (TMA) by fluorescence in situ hybridization (FISH) and calculated correlations with histoclinical features and prognosis. BAC probes were designed for: (i) two 8p12 subregions centered on RAB11FIP1 and FGFR1 loci, respectively; (ii) 11q13 region centered on CCND1; (iii) 12p13 region spanning NOL1; and (iv) three 20q13 subregions centered on MYBL2, ZNF217 and AURKA, respectively. Regions 8q24 and 17q12 were analyzed with MYC and ERBB2 commercial probes, respectively. Results We observed amplification of 8p12 (amplified at RAB11FIP1 and/or FGFR1) in 22.8%, 8q24 in 6.1%, 11q13 in 19.6%, 12p13 in 4.1%, 17q12 in 9.9%, 20q13Z (amplified at ZNF217 only) in 9.9%, and 20q13Co (co-amplification of two or three 20q13 loci) in 8.5% of cases. The 8q24, 12p13, and 17q12 amplifications were correlated with high grade. The most frequent single amplifications were 8p12 (9.8%), 8q24 (3.3%) and 12p13 (3.3%), 20q13Z and 20q13Co (1.6%) regions. The 17q12 and 11q13 regions were never found amplified alone. The most frequent co-amplification was 8p12/11q13. Amplifications of 8p12 and 17q12 were associated with poor outcome. Amplification of 12p13 was associated with basal molecular subtype. Conclusion Our results establish the frequencies, prognostic impacts and subtype associations of various amplifications and co-amplifications in breast cancers.